Automated universal BRAF state detection within the activation segment in skin metastases by pyrosequencing-based assay U-BRAFV600 - Skorokhod, Alexander; Helmbold, Peter; Brors, Benedikt; Schirmacher, Peter; Enk, Alexander; Penzel, Roland (PLOS ONE, 2013)
Malignant melanoma is a highly-aggressive type of malignancy with considerable metastatic potential and frequent resistance to cytotoxic agents. BRAF mutant protein was recently recognized as therapeutic target in metastatic melanoma. We present a newly-developed U-BRAFV600 approach - a universal pyrosequencing-based assay for mutation detection within activation segment in exon 15 of human braf. We identified 5 different BRAF mutations in a single assay analyzing 75 different formalin-fixed paraffin-embedded (FFPE) samples of cutaneous melanoma metastases from 29 patients. We found BRAF mutations in 21 of 29 metastases. All mutant variants were quantitatively detectable by the newly-developed U-BRAFV600 assay. These results were confirmed by ultra-deep-sequencing validation (∼60,000-fold coverage). In contrast to all other BRAF state detection methods, the U-BRAFV600 assay is capable of automated quantitative identification of at least 36 previously-published BRAF mutations. Under the precaution of a minimum of 3% mutated cells in front of a background of wild type cells, U-BRAFV600 assay design completely excludes false wild-type results. The corresponding algorithm for classification of BRAF-mutated variants is provided. The single-reaction assay and data analysis automation makes our approach suitable for the assessment of large clinical sample sizes. Therefore, we suggest U-BRAFV600 assay as a most powerful sequencing-based diagnostic tool to automatically identify BRAF state as a prerequisite to targeted therapy.